Experimental investigation into the use of collar for reducing scouring around short abutments. (2nd November 2021) - Hosseinjanzadeh, Hossein; Khozani, Zohreh Sheikh; Ardeshir, Abdollah; Singh, Vijay P
ABSTRACT: Scouring at bridge abutments undermines the stability of bridges. There are various methods to countermeasure the foundation of bridge abutments against scouring, but using a protective collar is one of the simplest methods. In this study, 60 tests were carried out experimentally under clear-water conditions. The maximum depth and time variation of local scour at vertical-wall, wing-wall and semi-circular short abutments were investigated. Experiments were conducted for uniform bed materials under four different flow intensities. Second, using collars of different sizes (as a ratio of abutment length) on various elevations of the bed (below, on, and top of the bed level), experiments were carried out again to investigate the effect of a collar on abutment scouring. Also, the effect of using partial collars was compared with full-collars for different abutment. Results showed that as the collar width increased, the scouring depth reduced suggesting that the width of collar was the most important factor for collar performance. The collar was more efficient in lower flow than in upper flow. The collar with 2.25 La in width situated under the bed elevation on the vertical wall and on streambed elevation on the wing-wall and semi-circular abutments reduced scour depth.